Feedback via Wikis: Revisions and Improvement - Zailin Shah, Yusoff (Association for the Advancement of Computing in Education (AACE), 2011)
This paper reports on the findings of a case study which explored the impact of using wikis as a tool in developing ESL students’ writing skills. Seventeen undergraduate students enrolled in a required final year course participated in this study. Data was triangulated using several data collection methods which included drafts written by students, feedback provided and the revisions done via wikis, and individual interviews. Findings showed that the students used most of the feedback they received via wikis to revise their reports. Revisions made resulted in writing improvement. Sixteen students showed statistically significant improvements in writing. The findings illustrates that wikis can be an effective tool for teaching writing because feedback and revisions can be easily reviewed and addressed using the facility provided by this editable, web-based tool.